BUDAYA KERJA GURU DI SEKOLAH DAERAH AGRARIS (STUDI SITUS DI SMP NEGERI 2 JATIROTO WONOGIRI) - SUPARNO , SUPARNO (2011)
The purpose of this study was to: 1) Describe the cultural characteristics of teachers and employees dressed in uniform SMP Negeri 2 Jatiroto; 2) Describe the characteristics of teachers and staff compliance culture SMP Negeri 2 Jatiroto at school organizational structure; 3) Describe the cultural characteristics of the friendship between teachers and employees of SMP Negeri 2 Jatiroto. This research is a qualitative ethnographic approach. Research carried out in SMP Negeri 2 Jatiroto Wonogiri. The research data collected in this study contains information on the results of participant observation and respondent's answer is the Principal and Teachers SMP Negeri 2 Jatiroto through interview. Sources of data in this study include: 1) The informant, who consist of the Principal , teachers, school staff , School Committee, and community sekitarInforman, which consists of the Principal, teachers, school staff, School Committee , and surrounding communities; 2) Archives and documents; 3) archives and documents owned by SMP Negeri 2 Jatiroto relating to the school profile, vision, and mission; 4) Places and events. Methods of data collection in this r esearch with interviews, participant observation and documentation. Based on the results of the study concluded that: 1) the culture of teacher dressed in uniforms tailored to the rules and regulations that have been defined by emphasizing the beauty, modesty, neatness and harmony of both individuals and groups; 2) teacher compliance culture in the organizational structure needs to be properly configured according to the distribution channel duties and authority of school organizations; 3) culture among teachers reflects the intimacy of friendship, togetherness, solidarity and mutual support in carrying out official duties or outside official work, mutual respect for both old and young .